Transition Intermediation in the Polish Food System - Kufel-Gajda, Justyna; Kryńska, Klaudia (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2025)
All over the world, we can observe the ongoing transition of agri-food sectors into sustainable food systems. Actors bridging stakeholders and their processes, thereby facilitating transitions, are called intermediaries. The wide variety of their missions, aims, and strategies creates so-called ecologies of intermediation. The main research question was how intermediaries could improve the facilitation of the transition to sustainable food systems in Poland. In order to do so, we analysed five intermediaries, each representing a different level of transition. We focused on organic food production, as organic certificates are commonly regarded as a sign of sustainable production. Understanding the ecologies of intermediation and increased support for activities and the establishment of intermediaries in the Polish food system should become the shared aim in governing the transition to a sustainable food system in Poland. In the public debate, we should highlight the modes, activities, and tasks of systemic, regime, niche, process, and user intermediaries, encouraging new and existing ones to develop, upscale, and intermediate between actors, networks, and institutions.